2021
DOI: 10.36076/ppj.2021.24.359
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Efficacy of Percutaneous Epidural Neurolysis of Adhesions in Chronic Lumbar Radicular Pain: 10 Year Follow-up of a Randomized Controlled Trial

Abstract: BACKGROUND: No long-term follow-up data exist in any treatment for chronic radicular pain occurring with disc pathology and after failed back surgery. A previous randomized controlled trial (RCT) has proven efficacy in short-term follow-up as an evidence-based effective therapeutic option. OBJECTIVES: Long term data is needed to determine the efficacy and cost- effectiveness of minimal invasive procedures. The present study reports 10 year follow-up results from the randomized trial. STUDY DESIGN: A prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…100,101 Clinical trials for herniated disc, spinal stenosis, and FBSS/PSPS have shown superiority of epidural adhesiolysis over conventional medical management, traditional ESI, and sham ESI. Gerdesmeyer published a 10-year follow-up 139 of his RCT comparing percutaneous adhesiolysis with placebo. 140 This study included operated and non-operated patients and showed significant improvement in the active group after 12 months.…”
Section: Epidural Adhesiolysis/epiduroscopymentioning
confidence: 99%
“…100,101 Clinical trials for herniated disc, spinal stenosis, and FBSS/PSPS have shown superiority of epidural adhesiolysis over conventional medical management, traditional ESI, and sham ESI. Gerdesmeyer published a 10-year follow-up 139 of his RCT comparing percutaneous adhesiolysis with placebo. 140 This study included operated and non-operated patients and showed significant improvement in the active group after 12 months.…”
Section: Epidural Adhesiolysis/epiduroscopymentioning
confidence: 99%
“…The last decade's medical literature considers EA the first Interventional treatment option for chronic lumbosacral radicular pain (CLSRP) [7,8]. One consistent randomized controlled trial of EA vs. placebo in treating CLSRP demonstrated the long-term efficacy of lumbar epidural lysis of adhesions in patients with chronic radicular pain with a 10-year follow-up [9].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple systematic reviews have summarized that the lysis procedure is now considered the first interventional treatment option for chronic lumbosacral radicular pain (CLSRP) [7,8]. A recent randomized study assessed the long-term efficacy of lumbar epidural lysis of adhesions in patients with chronic radicular pain with a 10-year follow-up [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is known to be effective in chronic lowback and lower limb pain. [15][16][17] The estimated incidence of adverse events after this procedure is up to 5%. 18 Complications are related to the intervention itself (and, for the most part, immediately apparent) or related to drug administration (typically emerging subsequently).…”
Section: Epidural Lysismentioning
confidence: 99%